Cytoglobin overexpression facilitates proliferation and migration of vascular smooth muscle cells - Li, Lei; Xie, Yilin; Shen, Li; Tan, Juanjuan; Qin, Yingchun; Yan, Zhiqiang (Archives of Biological Sciences, 2020)
Paper description: Cytoglobin is involved in injury-induced vascular remodeling. Decreased expression of cytoglobin was detected in the aorta of hypertensive rats compared to normotensive rats. Cytoglobin overexpression was capable of promoting proliferation and migration of vascular smooth muscle cells, and altering the expression of extracellular matrix components. Cytoglobin could play a role in pathological vascular remodeling. Abstract: Cytoglobin, a recently discovered globin, is expressed in vascular smooth muscle cells (VSMCs). Loss of cytoglobin provides a protective effect on vascular reconstruction but the effect of its overexpression is unclear. The aim of the study was to investigate the effect of cytoglobin overexpression on the migration and proliferation of VSMCs and possible mechanisms. We detected the expression of cytoglobin in hypertensive and normotensive rat aortas, with negative feedback regulation between cytoglobin and hypertension observed. The expression of cytoglobin was significantly decreased in hypertensive rats compared to normotensive rats, but VSMCs overexpressing cytoglobin displayed increased cell migration and proliferation, which led to a phenotypic switch. The increased expression of matrix metalloproteinase 9 and collagen Ia suggests a role for cytoglobin in extracellular matrix remodeling. Increased expression of proliferating cell nuclear antigen and decreased expression of p27 implies that cytoglobin is involved in modulating VSMC proliferation. Our findings indicate that cytoglobin may play an important role in vascular wall remodeling. https://doi.org/10.2298/ABS191024009L Received: October 24, 2019; Revised: February 15, 2020; Accepted: February 24, 2020; Published online: February 26, 2020 How to cite this article: Li L, Xie Y, Shen L, Tan J, Qin Y, Yan Z. Cytoglobin overexpression facilitates proliferation and migration of vascular smooth muscle cells. Arch Biol Sci. 2020;72(2):165-72.